PENGARUH PERTUMBUHAN PENJUALAN, INTENSITAS ASET TETAP, INTENSITAS MODAL, DAN KEPEMILIKAN KELUARGA TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Sektor Real Estate Dan Property Yang Terdaftar di BEI Periode Tahun 2018-2022) - Ramdani, Edon; Amelia, Rita (LPPM Universitas Putera Batam, 2023)
This research aims to analyze the influence of sales growth, fixed asset intensity, capital intensity, and family ownership on tax avoidance. This research was conducted by analyzing the financial reports of companies in the real estate and property sectors listed on the Indonesia Stock Exchange (BEI) during the period 2018 to 2022. The sample used in this research was 12 property sector companies listed on the Indonesia Stock Exchange during the period 2018 to 2022 using purposive sampling techniques. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The variables used in this research are Sales Growth) as the first independent variable, Fixed Asset Intensity as the second independent variable, Capital Intensity as the third independent variable, and Family Ownership as the fourth independent variable and Tax Avoidance as the dependent variable. The panel data regression method was used as the research methodology in this study. Analysis of research results using EViews 10 Student Version Lite software. The research results show that the best model is the Random Effect Model (REM). The results of this study show that Sales Growth partially has no effect on Tax Avoidance, Fixed Asset Intensity partially has an effect on Tax Avoidance, Capital Intensity has a partial effect on Tax Avoidance, Family Ownership has a partial effect on Tax Avoidance. However, simultaneously this research shows that Sales Growth, Fixed Asset Intensity, Capital Intensity, and Family Ownership have a simultaneous effect on Tax Avoidance. Keywords : Sales Growth, Fixed Asset Intensity, Capital Intensity, Family Ownership, Tax Avoidance